2015
DOI: 10.5327/z2447-2115201500040005
|View full text |Cite
|
Sign up to set email alerts
|

Perdas de massa muscular e adiposa após institucionalização: atenção aos mais idosos

Abstract: RESUMO INTRODUÇÃO: O envelhecimento provoca, simultaneamente, profundas mudanças na composição corporal e no estado nutricional do idoso. OBJETIVO: Avaliar as perdas de massas muscular e adiposa em residentes de uma Instituição de Longa Permanência para Idosos. MÉTODOS: Estudo observacional e longitudinal, com intervalo de três meses entre as duas avaliações. Participaram 34 idosos (média de idade: 81,8 anos; 23,5% homens; 76,5% mulheres), residentes em uma Instituição de Longa Permanência para Idosos de Teres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
7
1
Order By: Relevance
“…The high prevalence of excessive TSF in the elderly evidenced in this study differs from results obtained in other studies that verified high prevalence of insufficient TSF in the elderly 5,18 . This divergence evidences the specificity of certain physical characteristics, whether by regional or local issues; thus requiring individualized attention that aims to monitor the nutritional status of older adults enrolled in the Family Health Strategy of the city of Campina Grande/PB, since TSF is an evaluation variable that, when in excess, is a risk factor for cardiovascular and metabolic diseases.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The high prevalence of excessive TSF in the elderly evidenced in this study differs from results obtained in other studies that verified high prevalence of insufficient TSF in the elderly 5,18 . This divergence evidences the specificity of certain physical characteristics, whether by regional or local issues; thus requiring individualized attention that aims to monitor the nutritional status of older adults enrolled in the Family Health Strategy of the city of Campina Grande/PB, since TSF is an evaluation variable that, when in excess, is a risk factor for cardiovascular and metabolic diseases.…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding anthropometric variables, it was observed that overweight / obese individuals in this study were more likely of being dissatisfied with their body image compared to those with normal weight. This result is similar to that of other studies with older adults who found greater body image dissatisfaction among obese participants 2,14,19 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations